The mediating role of Market Orientation in the relationship between marketing capability and social capital on innovation performance - Arif, Nina Fapari; Wahyuningsih, Tri; Arifin, Andi Harmoko; Tasrim, Tasrim (UI Scholars Hub, 2025)
Abstract This study aims to examine the relationships among marketing capabilities, relational capital, market orientation, and innovation performance among Small and Medium Enterprises (SMEs) in Indonesia. A quantitative approach was employed, with data analyzed using the SEM-PLS (Structural Equation Modeling–Partial Least Squares) method via WarpPLS 8.0, which enables effective analysis of nonlinear relationships as well as mediation and moderation effects. The study population consists of SME actors in Indonesia, with a sample obtained through purposive sampling, involving a minimum of 180 respondents. The analysis results show that marketing capabilities have a significant positive effect on both market orientation and innovation performance, directly and indirectly through the mediation of market orientation. In contrast, while relational capital significantly influences market orientation, its direct effect on innovation performance is not statistically significant. The proposed model explains 69% of the variance in market orientation and 77% of the variance in innovation performance. This study underscores the importance of marketing capabilities and market orientation in enhancing innovation performance among SMEs, as well as the mediating role of market orientation in the relationship between relational capital and innovation performance. The findings provide practical implications for SME management, highlighting the need to strengthen marketing capabilities and manage external relationships to foster sustainable innovation. Keywords: Marketing Capabilities, Relational Capital, Market Orientation, Innovation Performance, SMEs.